Safety, efficacy, and tolerability of immune checkpoint inhibitors in the treatment of hepatocellular carcinoma. (June 2022) - Brown, Zachary J.; Gregory, Stephanie; Hewitt, D. Brock; Iacono, Stephen; Choe, Jennie; Labiner, Hanna E.; Pawlik, Timothy M.
Abstract: Hepatocellular carcinoma (HCC) is a major cause of mortality worldwide with an increasing incidence due to escalating rates of obesity and non-alcoholic fatty liver disease. Unfortunately, a majority of patients with HCC present with advanced disease. The immune checkpoint inhibitor atezolizumab, a PD-L1 inhibitor, in combination with bevacizumab, anti-VEGF, has become the new standard of care for patients with advanced HCC after demonstrating improved overall and progression free survival over sorafenib. In this review, we discuss the evolving role of immune checkpoint inhibitors in the treatment of HCC and their safety, efficacy, and tolerability. Highlights: Hepatocellular carcinoma is a major cause of mortality worldwide. A majority of patients with HCC present with advanced disease. The immune checkpoint inhibitor atezolizumab with bevacizumab is the new standard of care for patients with advanced HCC. There is an evolving role of immune checkpoint inhibitors in the treatment of HCC.